Excitation Functions for the Proton Irradiation on 45ScTarget - SHUKUR NOORI, Susan; AKKURT, İskender and DEMIR, Nurdan Karpuz (International Journal of Computational and Experimental Science and Engineering, 2019)
In the nuclear medicine for the positron emission tomography, the injected positron emitter leads to two 511 keV γ-rays. One of the most promising radionuclide is 45Sc. In this study, the main purpose was to investigate the excitation functions for the reactions 45Sc (p, x). TALYS 1.6 nuclear reaction simulation code was used for the excitation functions. These calculated excitation functions have been discussed and compared with each other and with Experimental Nuclear Reaction Data Library (EXFOR).